2004
DOI: 10.1063/1.1794858
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation contrast between biomolecular and inorganic materials at terahertz frequencies

Abstract: Wideband photomixing spectroscopy is used in the present work to contrast the transmission spectra of macromolecules commonly found in biomaterials such as potato starch, wheat flour and cornstarch, and proteins (Cytoplex™), and micromolecules such as sucrose, and inorganic materials such as sodium bicarbonate, and calcium sulfate. Powdered samples were measured at 0.1–0.5THz frequencies. A significant difference in attenuation is found between these samples. At 300GHz starch shows an absorption coefficient of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 2 publications
2
27
0
Order By: Relevance
“…Similar relationships between attenuation and terahertz frequency were found for other biomacromolecules, for example, THz attenuation in Cytoplex increases as 1.3 f [20]. Actually, the particle size for CS and PE powders were measured by using scanning electron microscopy (SEM), and the grain sizes were approximately 10 μm and 40 μm for CS and PE, respectively (see Fig.…”
Section: Mar 2018 | Biomedical Optics Express 1356supporting
confidence: 69%
See 1 more Smart Citation
“…Similar relationships between attenuation and terahertz frequency were found for other biomacromolecules, for example, THz attenuation in Cytoplex increases as 1.3 f [20]. Actually, the particle size for CS and PE powders were measured by using scanning electron microscopy (SEM), and the grain sizes were approximately 10 μm and 40 μm for CS and PE, respectively (see Fig.…”
Section: Mar 2018 | Biomedical Optics Express 1356supporting
confidence: 69%
“…The results may indicate that the THz attenuation caused by CS is mainly related to the scattering of THz radiation in the granular samples [19]. Several studies have been reported regarding the effects of granular solids on THz scattering [17,[20][21][22][23]. The equation below could be used to curve-fit the experimental data relating CS K (unit: cm −1 ) and frequency f (unit: THz) [22]:…”
Section: Relationship Between the Extinction Coefficient Of Cs And Thmentioning
confidence: 99%
“…The optimum hyperhemispherical offset in terms of Gaussicity and transmitted power is around r=n, where r is the radius of the lens and n is its index of refraction. 127 The free space THz beam can then be shaped and guided with parabolic mirrors or waveguides, 128 such as brass tube waveguides 129 or dielectric waveguides. 130,131 Due to the lack of low loss Terahertz materials, waveguides tend to be lossy and can only be used to cover short distances.…”
Section: -31mentioning
confidence: 99%
“…11 CW generation of THz radiation by photomixing (beating) of two infra-red laser sources commenced in the 1990's through the seminal work of Brown, McIntosh, and Verghese. 20 The technology for growth, design, and characterization of the Low Temperature Grown (LT) GaAs photomixers has improved dramatically 20,21 enabling the use of CW THz systems for sensing, spectroscopy, 13,22 and imaging applications. 23, , , , 24 25 26 27 The key materials component of LT-GaAs and higher power ErAs:GaAs photomixers is the presence of nanoparticulates that reduce the charge carrier lifetime in the material to the sub-picosecond level thereby enabling optical mixing to the THz range.…”
Section: Options For Imaging Modalitiesmentioning
confidence: 99%